2016
DOI: 10.1097/sga.0000000000000120
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Among Patients With Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a chronic disease of unknown etiology. The disease occurs early in life and the burden of symptoms is significant. Patients need to perform self-care to handle their symptoms, but knowledge about what kind of self-care patients do is limited and these individuals need to learn how to manage the symptoms that arise. The aim of this study was to explore self-care among patients with IBD. Twenty adult patients with IBD, 25–66 years of age, were interviewed. Data were analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
1
15
0
2
Order By: Relevance
“…A previous study revealed that physical activity could be useful for mitigating IBD symptoms and that low to medium intensity training had a positive effect on the psychological condition and improved the quality of life. It is necessary to find and evaluate the duration and intensity of physical activity for each individual IBD patient, which will have a positive effect on keeping the disease in remission ( 43 ). There are still no defined guidelines related to physical activity that could be recommended to all IBD patients, even though numerous studies have shown a beneficial and useful effect on the development and course of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that physical activity could be useful for mitigating IBD symptoms and that low to medium intensity training had a positive effect on the psychological condition and improved the quality of life. It is necessary to find and evaluate the duration and intensity of physical activity for each individual IBD patient, which will have a positive effect on keeping the disease in remission ( 43 ). There are still no defined guidelines related to physical activity that could be recommended to all IBD patients, even though numerous studies have shown a beneficial and useful effect on the development and course of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Resilient patients used a variety of methods to rebound from IBD. Our participants actively sought disease information [37]. The more knowledge the patients learned is, the easier it is to accept and manage IBD [38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies report that limited dietary guidance is provided to this population . Consequently, patients pursue advice from alternative health practitioners and various sources on the internet, many of which provide conflicting and misinformed dietary and supplement advice . The aim of this study is to describe the food avoidance patterns in IBD outpatients and specifically a) whether restriction is different in active disease versus remission; b) which foods are commonly avoided; and c) where patients obtain dietary information.…”
Section: Exploring Food Avoidance Behaviors In Outpatients With Inflamentioning
confidence: 99%